Isolation of Thermophilic Lignin Degrading Bacteria from Oil-Palm Empty Fruit Bunch (EFB) Compost - Lai, C.; Chua, H.; Danquah, M.; Saptoro, Agus (2017)
© Published under licence by IOP Publishing Ltd. Empty Fruit Bunch (EFB) is a potential and sustainable feedstock for bioethanol production due to its high cellulosic content and availability in Malaysia. Due to high lignin content of EFB and the lack of effective delignification process, commercial bioethanol production from EFB is presently not viable. Enzymatic delignification has been identified as one of the key steps in utilising EFB as a feedstock for bioethanol conversion. To date, limited work has been reported on the isolation of lignin degrading bacteria. Hence, there is a growing interest to search for new lignin degrading bacteria with greater tolerance to temperature and high level of ligninolytic enzymes for more effective lignin degradation. This study aimed to isolate and screen thermophilic ligninolytic microorganisms from EFB compost. Ten isolates were successfully isolated from EFB compost. Although they are not capable of decolorizing Methylene Blue (MB) dye under agar plate assay method, they are able to utilize lignin mimicked compound - guaiacol as a sole carbon on the agar plate assay. This infers that there is no correlation of ligninolytic enzymes with dye decolourization for all the isolates that have been isolated. However, they are able to produce ligninolytic enzymes (Lignin peroxidase, Manganese peroxidase, Laccase) in Minimal Salt Medium with Kraft Lignin (MSM-KL) with Lignin Peroxidase (LiP) as the predominant enzyme followed by Manganese Peroxidase (MnP) and Laccase (Lac). Among all the tested isolates, CLMT 29 has the highest LiP production up to 8.7673 U/mL following 24 h of growth.